Efektifitas Penggunaan Karbon Aktif Sebagai Filter Kompresor Untuk Penyelam Tradisional - Priyantini, Dwi; Farida, Imroatul (Sekolah Tinggi Ilmu Kesehatan Hang Tuah Surabaya, 2018)
The livelihood of the Indonesian people in the prominent grasslands is fishermen. Traditional fishermen to get a lot of fish, they use it using respiratory aids. Safety, the working health of traditional divers who breathe the burnt compressor and need to be handled properly because it can cause health problems and even death. The use of carbon as a filter that allows you to improve health status and prevent the death of traditional divers. For this reason, this study aims to prove the effectiveness of using filter filters on traditional divers. The method used to determine the concentration of O2 & CO2 gas in the economy on examination using sample gas before and after being given an activated carbon filter with a sample of 20 respondents. Statistical tests using Mann Whitney. The use of activated carbon filters has no effect on respiratory aids in traditional divers as evidenced by the Mann Whitney test showing p values at oxygen levels = 0.842 and p values at carbon dioxide levels = 0.300 ((p> Î± = 0.05). Activated carbon cannot be used as a respiratory aid for traditional divers and settlement of divers in traditionally carrying out effective and routine maintenance.Â Keywords: Traditional Divers, Compressors, Filters, Activated Carbon